Homicidios, ¿es ineluctable la violencia en América Latina? - Salama, Pierre (Frontera Norte, 2017)
En la mayoría de los países de América Latina la tasa de homicidios es mucho mayor que en los países desarrollados. En algunos países aumenta mientras en otros disminuye o bien se estabiliza. Se incrementa considerablemente en algunas grandes ciudades pero decrece significativamente en otras, desde inicios del año 2000. Los narcotraficantes y la evolución de las organizaciones criminales inciden de manera especial en todo ello. Las causas del aumento y la reducción de la violencia son múltiples y se entrecruzan. Reducir la violencia una vez que ha alcanzado el nivel que presenta en varios países de América Latina es un poco como tratar de “encontrar la cuadratura del círculo”. Eso da una idea del grado de dificultad. Algunas condiciones previas son necesarias para mejorar la cohesión social y para reducir la violencia: disminuir de manera sustancial las desigualdades socioeconómicas, favorecer una redistribución Homicides, Is violence ineluctable in Latin America? In most Latin American countries homicide rates are much higher than in developed countries. It increases in some countries, decreases in others or stabilizes. It growths strongly in a few cities but decrease significantly in others since the beginning of the years 2000. The drug taffickers and the evolution or criminal organizations play a special role.The causes of the increase and the reduction of violence are many and complexs. Reduce violence when it reaches the level that she knows in many Latin American countries is a bit like trying to do the squaring of the circle. That is the difficulty. There is a set of prerequisites to make the more cohesive society and reduce violence: substantially reduce socio-economic inequalities, promote a more egalitarian income distribution, develop a primary, secondary, and vocational quality education, invent the city policies, improve the quality of institutions, including and especially that of justice and the police, develop a policy of the city as it was done in Bogotá and as it starts to be done in the «pacified favellas» at the Brazil in contrast to what is observed in Mexico where repression is privileged and corruption is very high.